Proceedings of the 7th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2019
DOI: 10.7712/120119.7345.19771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Architectural Non-Structural Components on Lateral Behaviour of CFS Structures: Shake-Table Tests and Numerical Modelling

Abstract: This paper illustrates the effect of architectural non-structural components on the variation of dynamic properties and lateral seismic behaviour of Cold-Formed steel (CFS) buildings, using shake-table tests and numerical modelling. The seismic behaviour of a two-storey gypsum-sheathed building was investigated as a part of European project ELISSA. Shake-table tests were carried-out on this building under two different configurations: with and without architectural non-structural components. Dynamic properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Numerical analyses are a powerful tool in the investigation of the structural behavior; as indeed demonstrated by several studies [13][14][15][16][17][18][19][20], numerical investigation can accurately mimic experimental structural behavior. The modelling procedure introduces is in line with what was reported by the Authors [21,22] in previous research; therefore, hereinafter only the main information is reported.…”
Section: Modelling Proceduresmentioning
confidence: 99%
“…Numerical analyses are a powerful tool in the investigation of the structural behavior; as indeed demonstrated by several studies [13][14][15][16][17][18][19][20], numerical investigation can accurately mimic experimental structural behavior. The modelling procedure introduces is in line with what was reported by the Authors [21,22] in previous research; therefore, hereinafter only the main information is reported.…”
Section: Modelling Proceduresmentioning
confidence: 99%
“…Particularly, the architectural NSEs triples the lateral stiffness of building and reduce inter-storey drift by more than 2 times. [2]. Failure of acceleration sensitive NSEs occurs frequently after an earthquake because the dynamic features of the supporting structure are disregarded while calculating the seismic demand on NSEs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Steel structures are widely used in seismic areas since they guarantee ductile and dissipative behavior by means of localized plastic deformations [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Among the wide range of structural typologies, moment resisting frames (MRFs) are the most ductile due to redundancy that guarantees plastic redistribution in plastic hinges at the beam ends.…”
Section: Introductionmentioning
confidence: 99%